Reviews. (1st March 2015) - Hanlon, Dennis; Merás, Lidia; Moore, Andy; Mourenza, Daniel
Defa After East Germany, Brigitta B. Wagner (ED.) (2014) Rochester: Camden House, 349 pp., ISBN: 9781571135827, h/bk, £57.00La Televisión Durante La Transición Española, Manuel Palacio (2012) Madrid: Cátedra, 472 pp., ISBN: 9788437630687, h/bk, 22.90Experimental Film and Anthropology, Arnd Schneider and Caterina Pasqualino (EDS) (2014) New York and London: Bloomsbury, 208 pp., ISBN: 9780857858221, p/bk, £19.99On Slowness: Toward an Aesthetic of the Contemporary, Lutz Koepnick (2014) New York: Columbia University Press, 336 pp., ISBN: 9780231168328, h/bk, £24.00